THE STUDY OF INDONESIAN MOSLEM RESPONSES ON SALAFY- SHIA TRANSNATIONAL ISLAMIC EDUCATION INSTITUTION - Ali Muhtarom (Islam Futura, 2017)
This article describes the Indonesian Moslem responses to the institution of transnational Islamic education of Salafi and Shia in Indonesia. This can not be separated from the role of Saudi Arabia and Iran in the establishment of these educational institutions. The main objective of the Salafi’s education is to purify the form of Islam practiced by Indonesia Moslems. Meanwhile the main objective of the Shia’s education is to introduce the Shia Islamic thought, notably after the revolution of Iran in 1979. There are two responses on transnational Islamic Education from Indonesian Moslems. The first is rejection that represents the puritanist and traditionalist group. The puritanist group are DDII, Persis, Al-Irsyad, and FUUI. Shia Meanwhile, the traditionalist group especifically inherited by some figures of Nahdlatul Ulama as a form of maintaining the local religious tradition and culture. The second is acceptance that is shown by the moderate Moslems in Indonesia. This group includes Muhammadiyah and Nahdlatul Ulama that need to promote understanding of tolerance Shia.